Independent effects of mental fatigue and drop height on drop jump performance in American football athletes: an exploration of central-peripheral interaction - Wang, Zilong; Feng, Ziqi; Lu, Mengya; Sun, Jing; Liu, Tao; Zhang, Qiuxia; Wang, Xiangdong (PeerJ, 2026)
Background This study aimed to investigate the effects of mental fatigue (MF) and different drop heights on the athletic performance of American football players executing the drop jump (DJ) movement. Methods Twelve male American football athletes were selected as subjects. The Vicon infrared three-dimensional motion capture and analysis system, Kistler three-dimensional force platform, and other instruments were used. MF was induced through a Stroop task, and the DJ performance of the subjects was tested at drop heights of 30 cm, 40 cm, and 50 cm. A 2 × 3 repeated measures analysis of variance was employed. Results Regarding different jump heights, both under MF and baseline conditions, 40 cm and 50 cm heights resulted in lower jump heights compared to the 30 cm height (p = 0.002, p = 0.008); in terms of the rate of force development (RFD) metric, both under MF and baseline conditions, 40 cm and 50 cm heights showed lower RFD compared to the 30 cm height (p < 0.001); in the average power output metric, compared to the baseline, MF resulted in lower average power output across different drop heights (p < 0.001); in the reactive strength index (RSI) metric, compared to the baseline, MF resulted in lower RSI across different drop heights (p = 0.001), and compared to the 30 cm height, 40 cm and 50 cm heights showed lower RSI (p = 0.004, p = 0.008); in the Reactive Strength Ratio (RSR) metric, compared to the baseline, MF resulted in lower RSR across different drop heights (p = 0.001); in the Kleg metric, compared to the 30 cm height, 40 cm and 50 cm heights showed higher Kleg (p = 0.001, p = 0.008). Conclusions Under MF conditions, athletes’ performance in average power output, RSI, and RSR declined, suggesting a reduction in central nervous system efficiency. Additionally, increasing the drop height to 40 cm or above significantly reduced jump height and RFD, and increased Kleg. However, no interactive effects between MF and drop height were observed.
Keywords: Mental fatigue; Drop jump; Athletic performance; American football; Drop height